Site-specific demethylation and normal chromatin structure of the human dihydrofolate reductase gene promoter after transfection into CHO cells. - Shimada, T (1987)
The effect of in vitro methylation on the function and chromatin structure of the human dihydrofolate reductase (DHFR) promoter linked to the DHFR coding sequences (minigene) was studied after DNA-mediated gene transfer into DHFR- CHO cells. Methylation of HhaI sites reduced the transforming frequency to about 10% of control, whereas methylation of HpaII sites had a less significant effect. The integrated genes were demethylated at specific sites in the promoter sequence, namely, HpaII sites around -57 base pairs from the major start site for transcription and HhaI sites around +9, +24, or both. All other HpaII or HhaI sites in the DHFR coding region or in the plasmid sequences remained consistently methylated. The DHFR minigene, after methylation with HhaI methylase, was also introduced without selection by cotransfection with pSV2neo and selection for neor clones in G418. Preferential demethylation of the same sites was observed even without selection for the DHFR+ phenotype. Analysis of the chromatin structure of the integrated minigene revealed characteristic proximal and distal hypersensitive regions of the promoter, as previously observed in human cells. Correctly initiated DHFR mRNA was detected in all of the transformants studied. These results suggest that formation of the characteristic chromatin structure is an intrinsic property of the DHFR promoter sequence and that demethylation of specific sites accompanies gene expression.